The Image of a Nation in Angie Thomas’s The Hate U Give (2017) - Matek, Ljubica; POLJAK REHLICKI, Jasna (Anafora, 2023)
The paper offers an imagological analysis of Thomas’s debut novel The Hate U Give (2017) with the aim of showing that the cultural image of the Black race is a firmly rooted construct in the United States. The analysis is based on the ideas proposed by Benedict Anderson in his Imagined Communities: Reflections on the Origin and Spread of Nationalism (2006) and suggests that despite the well-established theoretical ideas of American-ness and the greatness of the American nation, there is no single nation to speak of in the US society. Anderson suggests that the society has preconceived beliefs on members of certain (racial, ethnic) groups, which the novel clearly depicts through the novel’s protagonist, Starr Carter, who engages in code switching in order to get a better education and, thus, a chance for success outside of the black ghetto. The pre-established notions and stereotypes, often promoted via populist discourse of the dominant group, prevent unification of people into a nation and at the same time give rise to nationalism, racism, and hatred.